miRNA-194-3p represses NF-κB in gliomas to attenuate iPSC genes and proneural to mesenchymal transition - John Ryan Jacob; Rajbir Singh; Masa Okamoto; Arnab Chakravarti; Kamalakannan Palanichamy (iScience, 2024)
Summary: Severe tumor heterogeneity drives the aggressive and treatment refractory nature of glioblastomas (GBMs). While limiting GBM heterogeneity offers promising therapeutic potential, the underlying mechanisms that regulate GBM plasticity remain poorly understood. We utilized 14 patient-derived and four commercially available cell lines to uncover miR-194-3p as a key epigenetic determinant of stemness and transcriptional subtype in GBM. We demonstrate that miR-194-3p degrades TAB2, an important mediator of NF-κB activity, decreasing NF-κB transcriptional activity. The loss in NF-κB activity following miR-194-3p overexpression or TAB2 silencing decreased expression of induced pluripotent stem cell (iPSC) genes, inhibited the oncogenic IL-6/STAT3 signaling axis, suppressed the mesenchymal transcriptional subtype in relation to the proneural subtype, and induced differentiation from the glioma stem cell (GSC) to monolayer (ML) phenotype. miR-194-3p/TAB2/NF-κB signaling axis acts as an epigenetic switch that regulates GBM plasticity and targeting this signaling axis represents a potential strategy to limit transcriptional heterogeneity in GBMs.